2021
DOI: 10.1002/ijc.33584
|View full text |Cite
|
Sign up to set email alerts
|

A rare variant in EZH2 is associated with prostate cancer risk

Abstract: Prostate cancer (PrCa) is highly heritable, and although rare variants contribute significantly to PrCa risk, few have been identified to date. Herein, whole-genome sequencing was performed in a large PrCa family featuring multiple affected relatives spanning several generations. A rare, predicted splice site EZH2 variant, rs78589034 (G > A), was identified as segregating with disease in all but two individuals in the family, one of whom was affected with lymphoma and bowel cancer and a female relative. This v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The Tasmanian PrCa resource includes a rare collection of 73 Caucasian PrCa families from the founder population of Tasmania, as previously described 16,17 . This study focused on family PcTas9 (Figure ), in which 61 cases of PrCa have been identified through the Tasmanian Cancer Registry.…”
Section: Methodsmentioning
confidence: 99%
“…The Tasmanian PrCa resource includes a rare collection of 73 Caucasian PrCa families from the founder population of Tasmania, as previously described 16,17 . This study focused on family PcTas9 (Figure ), in which 61 cases of PrCa have been identified through the Tasmanian Cancer Registry.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor samples were sourced from two Australian studies, the Tasmanian Familial Prostate Cancer Cohort and the population‐based Tasmanian Prostate Cancer Case–Control Study , both of which have been described previously 7–10 . Familial PrCa is defined as families with two or more affected first‐degree relatives.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor samples were sourced from two Australian studies, the Tasmanian Familial Prostate Cancer Cohort and the population-based Tasmanian Prostate Cancer Case-Control Study, both of which have been described previously. [7][8][9][10] Familial PrCa is defined as families with two or more affected first-degree relatives. Archived prostate tissue pathology blocks from familial and sporadic PrCa cases were collected from local pathology laboratories.…”
Section: Australian Prostate Tumor Samplesmentioning
confidence: 99%
“…Thus, EZH2 inhibitors are potential candidates for CRPC therapies. Two EZH2 variants (rs78589034 90 and rs2302427 91 ) are associated with increased prostate cancer risk.…”
Section: Histone Methyltransferases/demethylases In Prostate Cancermentioning
confidence: 99%